2019
DOI: 10.4178/epih.e2019051
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of early initiation of breastfeeding in Peru: analysis of the 2018 Demographic and Family Health Survey

Abstract: OBJECTIVES: Early initiation of breastfeeding (EIBF) is one of the most cost-effective strategies to reduce neonatal mortality. We sought to determine the prevalence and determinants of EIBF in Peru.METHODS: We performed a cross-sectional analytical study of the 2018 Peruvian Demographic and Family Health Survey as a secondary data source. In total, 19,595 children born during the 5 years prior to the survey were included in the study. The dependent variable (EIBF status), socio-demographic variables, and preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 30 publications
3
16
0
5
Order By: Relevance
“…The study at hand revealed that women who delivered at a health facility were more likely to initiate breast feeding within the first 1 hour of birth than their counterparts. This finding is in line with studies conducted in South Ethiopia, 41 Northwest Ethiopia, 26 38 Economic Community of West African States, 45 sub-Saharan Africa, 33 Peru 46 and Romania. 47 As it is stated in literature, initiation of breast feeding within the first hour of birth is an integral part of the safe delivery procedure.…”
Section: Discussionsupporting
confidence: 92%
“…The study at hand revealed that women who delivered at a health facility were more likely to initiate breast feeding within the first 1 hour of birth than their counterparts. This finding is in line with studies conducted in South Ethiopia, 41 Northwest Ethiopia, 26 38 Economic Community of West African States, 45 sub-Saharan Africa, 33 Peru 46 and Romania. 47 As it is stated in literature, initiation of breast feeding within the first hour of birth is an integral part of the safe delivery procedure.…”
Section: Discussionsupporting
confidence: 92%
“…This might mean that female education as a means of promoting timely initiation of breast feeding may only be impactful until primary schooling, the point after which the impact may not be absent. Findings similar to this have been reported from sub-Saharan Africa and elsewhere 19 23. From these findings, it can be said that increasing the educational status of mothers improves EIBF only until primary school.…”
Section: Discussionsupporting
confidence: 86%
“…Though studies have shown that maternal education significantly improves EIBF and EBF,14–16 this effect has not been consistently reported across studies. While several studies reported a positive association between maternal education and EIBF14 17 and EBF,15 others reported that maternal education, after a certain level, either has no association or a negative association with EIBF and EBF 11 18–20. Thus, it is essential to assess the effects of maternal education on EIBF and EBF by using a representative and large sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Hence it is important to adjust all maternity hospital settings to facilitate EIBF by making it a very easy choice for the mother. Enhancing EIBF through maternity services-based interventions would indeed be a cost-effective approach to improve postpartum mood and could help alleviate the influence of EMCS on PPD risk, at least to some extent [ 48 ].…”
Section: Discussionmentioning
confidence: 99%